Presarcopenia and its Impact on Disability in Female Patients With Rheumatoid Arthritis - Meltem ALKAN MELİKOĞLU, (Archives of Rheumatology, 2017)
Objectives: This cross-sectional pilot study aims to investigate presarcopenia in female patients with rheumatoid arthritis (RA) and to evaluate its relationship to the disability assessment. Patients and methods: Forty female patients with RA (mean age 48.29±8.34; range 31 to 66 years) and 40 healthy controls (mean age 46.21±6.90; range 31 to 58 years) matched for age, sex, and body mass index were included. Pain, morning stiffness duration, disease activity score, erythrocyte sedimentation rate, C-reactive protein, and Health Assessment Questionnaire (HAQ) were evaluated. Body compositions were assessed with whole body dual energy X-ray absorptiometry. The appendicular skeletal muscle mass and skeletal muscle mass index (SMI) of RA patients were compared to the controls and possible correlations between SMI, disease characteristics, and HAQ score were investigated. Results: The body mass index values and percentages of obese, overweight, and healthy weight subjects were similar in the patient and control groups. However, appendicular skeletal muscle mass and SMI calculations were significantly lower, and the percentage of presarcopenia was significantly higher in patients with RA (20%) than controls (7%) (p<0.05). Although there was no significant correlation between SMI and other parameters, a significant negative correlation was determined between SMI and HAQ score in patients with RA (p<0.05). Conclusion: We demonstrated lower SMI values and higher presarcopenia ratios in patients with RA than healthy controls. Independent from other disease characteristics, the inverse correlation between SMI and HAQ scores may contribute to understanding of the impact of the process on patient disability.